1999
DOI: 10.1007/s100380050114
|View full text |Cite
|
Sign up to set email alerts
|

A novel therapeutic trial of homogentisic aciduria in a murine model of alkaptonuria

Abstract: Alkaptonuria is a rare autosomal recessive disorder characterized by homogentisic aciduria, ochronosis, and arthritis. Although a deficiency of homogentisic acid 1,2-dioxygenase has recently been confirmed at the molecular level, no effective treatment regimen has yet been developed for this disorder. In the present study, 2(-2-nitro-4-trifluoromethylbenzoyl)-1,3-cyclohexanedione (NTBC), a potent inhibitor of p-hydroxyphenylpyruvate dioxygenase (which catalyzes the formation of homogentisic acid from phydroxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…İdrarda HGA atılımını azaltmak için yük-sek doz C vitamini verilmesi, tirozin ve fenilalaninden fakir, düşük proteinli diyet ve NTBC (Nitrotrifluoromethylbenzoylcyclohexanedione) önerilen ancak uzun dönem sonuçları ve klinik etkinliği bilinmeyen tedavi yöntemle-ridir (14). HGA oksidaz enzimini rekombinan teknoloji ile yerine koyma gelecek için ümit veren bir tedavi seçene-ği olabilir (11,15). Okronotik artropati dejeneratif bir artrittir, erken dönemde analjezikler, steroid olmayan antienflamatuvar ilaçlar ve fizik tedavi ile semptomatik tedavi yapılsa da ilerlemiş diz ve kalça tutulumlarında kalça ve diz artroplastisi önerilmektedir (17)(18)(19).…”
Section: Discussionunclassified
“…İdrarda HGA atılımını azaltmak için yük-sek doz C vitamini verilmesi, tirozin ve fenilalaninden fakir, düşük proteinli diyet ve NTBC (Nitrotrifluoromethylbenzoylcyclohexanedione) önerilen ancak uzun dönem sonuçları ve klinik etkinliği bilinmeyen tedavi yöntemle-ridir (14). HGA oksidaz enzimini rekombinan teknoloji ile yerine koyma gelecek için ümit veren bir tedavi seçene-ği olabilir (11,15). Okronotik artropati dejeneratif bir artrittir, erken dönemde analjezikler, steroid olmayan antienflamatuvar ilaçlar ve fizik tedavi ile semptomatik tedavi yapılsa da ilerlemiş diz ve kalça tutulumlarında kalça ve diz artroplastisi önerilmektedir (17)(18)(19).…”
Section: Discussionunclassified
“…Development of the active compound may result in the first pharmacotherapeutic agent for this metabolic disease. 9 No benefits have been received or will be received from a commercial party related directly or indirectly to the subject of this article.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotheses as to why this occurred, aside from the production of ascorbic acid in mice, have stated that the mice do not live long enough for ochronosis to occur and that urinary excretion is efficient so that tissues are not exposed to the high concentration of HGA as seen in humans. 60,61 Other animal models have produced similar reports, although arguably not as reliable. 54 Contrary to the above reports, Taylor et al produced the first data of tissue ochronosis in a murine model.…”
Section: Models Of Akumentioning
confidence: 99%
“…The conclusions from these studies suggest beginning therapy at an early stage in the development of ochronosis results in a more beneficial outcome. 48,61 Initial trials of low dose NTBC in two patients with AKU showed a 69% reduction in urinary HGA excretion. However, there was a significant elevation in plasma tyrosine levels, increasing the risk of corneal crystal formation, corneal epithelial damage, and photophobia.…”
Section: Models Of Akumentioning
confidence: 99%